2012
DOI: 10.2175/193864712811708419
|View full text |Cite
|
Sign up to set email alerts
|

<I>Thauera</I> spp., Another Prominent Denitrifying Bacteria in the Methanol-Fed Activated Sludge

Abstract: Using quantitative polymerase chain reaction techniques, we quantified three denitrifying genera Paracoccus, Thauera and Pseudomonas. Thauera spp. (3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The rarefaction analysis was conducted using Mothur v.1.21.1 to reveal the diversity indices including the Chao and Shannon diversity indices (Schloss PD et al, 2009). To detect the influence of wastewater discharge on benthic microbial community composition, the relative abundances of sewer infrastructure-associated bacterial genera (i.e., Acinetobacter, Arcobacter and Trichococcus) (VandeWalle et al, 2012;Newton et al, 2013), denitrifying genera (i.e., Comamonas, Hyphomicrobium, Paracocccus, Thauera and Zoogloea) that have been found in the activated sludge of WWTPs (Tsai et al, 2012;Wang et al, 2014), and potential bacterial pathogen sequences suggested by Ibekwe et al (2016) were analysed in the present study. To examine the dissimilarity of microbial community between sampling sites or seasons, a PCA was performed based on the OTU…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rarefaction analysis was conducted using Mothur v.1.21.1 to reveal the diversity indices including the Chao and Shannon diversity indices (Schloss PD et al, 2009). To detect the influence of wastewater discharge on benthic microbial community composition, the relative abundances of sewer infrastructure-associated bacterial genera (i.e., Acinetobacter, Arcobacter and Trichococcus) (VandeWalle et al, 2012;Newton et al, 2013), denitrifying genera (i.e., Comamonas, Hyphomicrobium, Paracocccus, Thauera and Zoogloea) that have been found in the activated sludge of WWTPs (Tsai et al, 2012;Wang et al, 2014), and potential bacterial pathogen sequences suggested by Ibekwe et al (2016) were analysed in the present study. To examine the dissimilarity of microbial community between sampling sites or seasons, a PCA was performed based on the OTU…”
Section: Discussionmentioning
confidence: 99%
“…Restoration activities, thus, are recommended to restore the ecosystem quality in these waterways. All these genera are have been reported in the active sludge (Juretschko et al, 2002;Tsai et al, 2012;Wang et al, 2014). Table S4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations